Price Signal of Tradable Guarantees of Origin for Hedging Risk of Renewable Energy Sources Investments - Dagoumas, Athanasios S.; Koltsaklis, Nikolaos E. (International Journal of Energy Economics and Policy, 2017)
The risk of renewable energy sources (RES) investments in several European Union (EU) countries is offset by site-specific compensation, resulted by competitive auctions according the EU state aid guidelines for energy for the period 2014-2020. However, this scheme of incentivizing RES will probably be replaced, inheriting risk for RES investments. A potential market-based scheme could be the introduction of tradable guarantees of origin (GOs). This paper uses an integrated model, integrating the optimal power systems expansion planning problem with the unit commitment problem, which performs the simulation of the day-ahead electricity market. The model is used for the expansion of the Greek power system, identifying the RES capacity mix per technology type. The model estimates the new RES capacity, the evolution of the day-ahead price and the levelized cost of avoided energy. This enables the identification of the remuneration of RES producers from the wholesale market and the premium required for covering their levelized cost of electricity. The estimation of this premium provides insights on the price signals of tradable GOs, which could offset the risk of RES investments. The paper finally discusses the GOs’ status and challenges, towards becoming the preferred policy for RES promotion. Keywords: Renewable Energy Sources, Guarantees of Origin, Risk, Power System Expansion Planning, Feed-in-Tariff, State Aid Guidelines JEL Classifications: Q4, Q42